Implementasi Model Pembelajaran Berbasis Proyek dalam Meningkatkan Kreativitas Mahasiswa - Ageng Satria Pamungkas; Trisna Rukhmana; Zahlimar Zahlimar; Kadirun Kadirun; Mukhtar Zaini Dahlan; Kusuma Wardany (Departement of Mathematics Education, 2024)
Project-Based Learning Models (PBP) have received significant attention in higher education contexts due to their potential to stimulate student creativity. This research explores the impact of PBP implementation in increasing student creativity. Through a qualitative approach, data was collected from research participants who were students who had participated in learning experiences with PBP. The research results showed that the majority of students expressed increased creative skills, including the ability to think out-of-the-box, face challenges with innovative solutions, and integrate various concepts to create new solutions. In addition, they also feel more motivated and actively involved in learning because the projects they participate in allow them to be involved in situations that are similar to real life. Collaboration between students also plays an important role in stimulating creativity, enabling the exchange of ideas, mutual support, and exploring innovative solutions. Lecturers and educational policy makers need to consider integrating PBL in curriculum design and learning practices to prepare students to face the demands of an increasingly complex world of work with high levels of creativity and confidence. In conclusion, PBP not only increases students' creativity, but also helps them apply theoretical knowledge in relevant and real contexts.